Szanse i zagrożenia rozwoju koncepcji Big Data na przykładzie sektora publicznego - Burzyński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Big Data market is an important branch in the development of the modern digital economy. The growing rate of people using the Internet and various online tools makes the image of the Web changeconstantly, entailing among other things, the increasing amount of data generated, and therefore aggregated and processed by the companies each day. Public sector entities recognize the possibility of using Big Data as well, which in turn can contribute to an increase in economic growth. Theproblem of the concept of Big Data in the functioning of the government is much wider than in the case of commercial entities. This is due both to the amount and complexity of the data processed, and the need to use them in aunified system. Athreat to further development of this tool may be citizens’ fears of excessive interference of the authorities in their private life, hence it seems necessary to create appropriate legal regulations defining the possibilities of obtaining and processing data by certain public sector entities.
Keywords: gospodarka cyfrowa; dane osobowe; nowe technologie; sieci społecznościowe